NOVEL SYNTHETIC AMINO ACIDS AND PEPTIDES AS BACTERIAL GROWTH INHIBITORS (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
The influence of novel synthetic amino acids and peptides on the growth of bacteria included in test culture collection has been studied. The compounds were revealed to inhibit the growth of all the strains included in collection. Some compounds demonstrated antibacterial activity in relation to antibiotic-resistant E.coli strains, others demonstrated the specificity in relation to particular species. Thus, the novel synthetic inhibitors of bacterial growth, including antibioticresistant ones, were described.
Keywords: non-protein amino acids, peptides, plasmid-antibiotics, alanine analog, antibiotic-resistant $E.~coli$ strains